2005
DOI: 10.1074/jbc.m500817200
|View full text |Cite
|
Sign up to set email alerts
|

Backbone-methylated Analogues of the Principle Receptor Binding Region of Human Parathyroid Hormone

Abstract: We have used backbone N-methylations of parathyroid hormone (PTH) to study the role of these NH groups in the C-terminal amphiphilic ␣-helix of PTH (1-31) in binding to and activating the PTH receptor (P1R). The circular dichroism (CD) spectra indicated the structure of the C-terminal ␣-helix was locally disrupted around the methylation site. The CD spectra differences were explained by assuming a helix disruption for four residues on each side of the site of methylation and taking into account the known depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
4
13
0
Order By: Relevance
“…This observation raised the possibility that the C-terminal binding domain of PTH can functionally interact with the receptor J domain. Consistent with this possibility, we recently showed that methylation of several backbone nitrogen atoms in region 17-31 of PTH-(1-31) impairs, albeit modestly, the capacity of the ligand to stimulate cAMP formation in cells expressing PTHR-delNt (8). Taken together, these observations point to the uncertainty that exists in our understanding of the specific mechanisms by which the C-terminal domain of PTH contributes to the PTHR-binding process.…”
Section: Parathyroid Hormone (Pth)mentioning
confidence: 53%
See 1 more Smart Citation
“…This observation raised the possibility that the C-terminal binding domain of PTH can functionally interact with the receptor J domain. Consistent with this possibility, we recently showed that methylation of several backbone nitrogen atoms in region 17-31 of PTH-(1-31) impairs, albeit modestly, the capacity of the ligand to stimulate cAMP formation in cells expressing PTHR-delNt (8). Taken together, these observations point to the uncertainty that exists in our understanding of the specific mechanisms by which the C-terminal domain of PTH contributes to the PTHR-binding process.…”
Section: Parathyroid Hormone (Pth)mentioning
confidence: 53%
“…The instrument was calibrated with ammonium (ϩ)-10-camphorsulfonate. Data are expressed as the number of helical residues/peptide chain as calculated from Ϫ[] 222 ϫ 30/28,000, where [] 222 is the mean residue ellipticity at 222 nm, as we described previously (8).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a methylation site can therefore be expected to be reflected in the masses of the cand z-ions that contain the methylation site, as is the case with side-chain post-translational modifications. While the methyl modification is expected to be strongly bound, its presence on the amide nitrogen might have been expected to affect the overall ETD process, at least based on one proposed mechanism for ECD/ETD [18]. N-methylation affects modestly the relative abundances of the sequence informative fragment ions but this observation may very well result from conformational differences between modified and unmodified versions of the peptide cations.…”
Section: Discussionmentioning
confidence: 99%
“…ECD [9 -12] and ETD [13] have already been shown to be effective in identifying side-chain and N-terminal methylation in histones, for example. Amide nitrogen methylation occurs in nature, such as in bacterial and fungal peptides/proteins that have possible medicinal properties [14 -17], and has been used as a tool for protein binding studies [18]. The dissociation behavior of N-methylated peptide ions subjected to collisional activation has been reported, and it was noted that there was an increase in relative abundance of the products coming from cleavage of the amide bond at the methylation site [19,20].…”
mentioning
confidence: 99%
“…The crystal structure of the PTH1R extracellular domain-PTH(15-34) complexes provides direct evidence for the model that the C-terminal domain of the ligand binds to the N terminus of the receptor, thus positioning the N terminus of the ligand at a favorable distance to allosterically activate the J-domain of the receptor (52). Therefore, it is interesting to compare the data from photoaffinity cross-linking of PTH1R (22)(23)(24)(25)(53)(54)(55)(56)(57)(58)(59)(60) with those of CRFR1. Similar to our finding that residues 16 and 17 of sauvagine cross-link to the J-domain of CRFR1, residues within the C terminus of PTH , such as 19 and 27, are reported to cross-link to the second transmembrane domain and within the first extracellular loop, respectively; both are within the J-domain of PTH1R (58).…”
Section: Discussionmentioning
confidence: 99%